The importance of crop improvement in conservation of diversity - Adhikary, K.C.; Adhikary, S.P.; Adhikary, K.R. (CGIAR Systemwide Program on Participatory Research and Gender Analysis for Technology Development and Institutional Innovation, 2001)
In this paper, fanners describe the agro ecology of Bagnas and the diversity of crops grown there.